Adult Plant Leaf Rust Resistance Derived from the Soft Red Winter Wheat Cultivar 'Caldwell' Maps to Chromosome 3BS. Issue 1 (1st January 2018) - Kolmer, J. A.; Chao, S.; Brown‐Guedira, G.; Bansal, U.; Bariana, H.
ABSTRACT: 'Caldwell' is a US soft red winter wheat ( Triticum aestivum L.) that has partial, adult plant resistance to the leaf rust pathogen Puccinia triticina Eriks. A line of 'Thatcher∗2/Caldwell' with adult plant resistance derived from Caldwell was crossed with 'Thatcher' to develop a population of recombinant inbred lines (RILs). The parents and RIL population were evaluated for segregation of leaf rust resistance in four field tests. A genetic map of the RIL population was constructed using 90K single‐nucleotide polymorphism (SNP) markers with the Illumina Infinium iSelect 90K wheat bead array. Significant effects for reduction of leaf rust severity in all four tests were found for a quantitative trait locus on chromosome 3BS. Simple sequence repeat (SSR) markers linked to the adult plant resistance gene Lr74 and kompetitive allele specific polymerase chain reaction (KASP) assay markers were added to the map on chromosome 3BS. Thatcher and the resistant Thatcher∗2/Caldwell parent were negative for the presence of Sr2 on chromosome 3BS based on the tightly linked marker csSr2 . The SSR marker cfb5006 linked closely to Lr74 mapped the closest to the logarithm of odds peak for leaf rust resistance on chromosome 3BS. The SNP and SSR markers on chromosome 3BS can be used to add Caldwell leaf rust resistance to wheat breeding germplasm.